2019
DOI: 10.1111/hae.13871
|View full text |Cite
|
Sign up to set email alerts
|

ST‐Segment Elevation Myocardial Infarction (STEMI) and Pulmonary Embolism in a Hemophilia A Patient Receiving Emicizumab and recombinant Activated Factor VII

Abstract: Congenital haemophilia A is a bleeding disorder affecting roughly 1 in 5000 male children with a prevalence of around 160 000 people worldwide. 1 As a result of treatment, approximately 20%-30% of patients with haemophilia A develop allo-immune antibodies inhibiting exogenous coagulation factor VIII. For such patients before 2017, if they failed immune tolerance induction, activated prothrombin complex concentrate [aPCC; factor eight inhibitor bypassing activity (FEIBA),Takeda] for prophylaxis or on-demand and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…Notably, both thrombosis and TMA have been reported in adolescent and adult patients who received emicizumab concomitantly with APCC 15 or rFVIIa 32 . Therefore, we currently suggest routine blood counts and renal function tests for TMA screening to be performed in patients being co‐administered with bypass agents.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, both thrombosis and TMA have been reported in adolescent and adult patients who received emicizumab concomitantly with APCC 15 or rFVIIa 32 . Therefore, we currently suggest routine blood counts and renal function tests for TMA screening to be performed in patients being co‐administered with bypass agents.…”
Section: Discussionmentioning
confidence: 99%
“…There is one report of non-STelevation myocardial infarction and pulmonary embolism associated with co-administration of rFVIIa. 41 No thrombotic events have been reported in association with FVIII replacement, although the numbers treated to date are low and data in young children are very limited. 42,43 Recurrence of inhibitors in people previously tolerized to FVIII…”
Section: Thrombosismentioning
confidence: 99%
“…A mechanism of TMA development in which enhanced thrombin generation does not seem to play the primary role has not yet been described. It is worth mentioning that one severe haemophilia A patient with inhibitor, who received recombinant activated factor VII (rFVIIa) during emicizumab prophylaxis, experienced myocardial infarction without ST-segment elevation and pulmonary embolism [25]. Up to date however, no thromboembolic complications or TMA cases have been reported for hemophilia A patients with inhibitor during concomitant administration of emicizumab and factor VIII concentrates [26,27].…”
Section: Safety Profile Of Emicizumab For Patients With Hemophilia a mentioning
confidence: 99%
“…HAVEN 1 trial, thromboembolic events and TMA were described only in patients who receivied emicizumab in concomitance with aPCC at a dose > 100 U/kg for > 24 h. In the HAVEN program, there were no reports on thromboembolic events or thrombotic microangiopathy in patients on emicizumab prophylaxis in concomitance with rFVIIa. Outside the clinical trials however, one case of thromboembolic complications was reported in a patient who was on emicizumab prophylaxis after rFVIIa administration) [25].…”
Section: Management Of Acute Bleeding In Inhibitor Patients On Emmentioning
confidence: 99%
See 1 more Smart Citation